Analisis Kualitas Situs Web Pejabat Pengelola Informasi Dan Dokumentasi (PPID) Perpustakaan Nasional RI Menggunakan Netqual - Arwan Subakti; Wisnu Ananta Kusuma; Badollahi Mustafa (Perpustakaan IPB, 2016)
Government and public service systems in the E-Government era are demanded to be transparent, effective, efficient, accountable and useful in society. These are the challenges that has to be faced by government institutions in conducting their functions. The rapid advance of information and communications technology opens the opportunity in accessing, processing and using the information fast and accurately. This research aims to analyze customer satisfaction towards Information and Documentation Management Officer (IDMO) Perpusnas RI website quality (http://ppid.perpusnas.go.id/). Electronic service quality model used in this research is NetQual (Bressolles, 2006) consisting of 18 variables representing five dimensions of service quality, namely information, ease of use, design, reliability, dan privacy/security. This research used quantitative descriptive approach supported with survey of 48 respondents who have accessed PPID Perpusnas RI website. This research used two methods in analyzing data, customer satisfaction index and importance performance analysis. The result indicated that overall user was not satistified with PPID Perpusnas RI website, with customer satisfaction index 39,71 % (very poor). It is also parallel with analysis result of importance performance rate whose gap ranges from -015 to -1,23 with average total score is -0,85. It could be concluded that customer respondents generally has not satisfied with the quality of PPID Perpusnas RI website.Keywords: Customer Satisfaction Index, Importance Performance Analysis, NetQual, PPID, Public Information, Website Quality